Orientation of Stylistics Teaching for Non-Arabic Speakers - Hani'atul Khoiroh (JEET, Journal of English Education and Technology, 2023)
This research aims to present aspects related to stylistics teaching including its concept, objectives, subjects, methodology, evaluation, and orientation in teaching. The researcher employed a descriptive method, specifically desk-based research using document analysis and qualitative descriptive analysis in three steps: data condensation, presentation, and conclusion. The result obtained indicates that stylistics teaching is an organized process conducted by teachers to transfer information, knowledge, and rhetorical skills to students while developing their attitudes towards it. The objectives of stylistics teaching include enlightening students about the principles and foundations upon which eloquence in speech, stylistic quality, and content rely, such as the science of meanings, expression, literary embellishments, and the method employed, either inductive/deductive or analytical/standardized. Evaluation methods encompass formative and summative assessments. Orientation is provided not to isolate the learning material as a separate grammar subject but to integrate it within the context of literary texts, whether poetic or prose, classical or modern, including Quranic or contemporary literature. Its is aimed at contributing to the formation and development of literary taste among students while acquainting them with the secrets of rhetorical miracles."